A Novel Pain Interprofessional Education Strategy for Trainees: Assessing Impact on Interprofessional Competencies and Pediatric Pain Knowledge - Judith P. Hunter (Pain Research and Management, 2015)
BACKGROUND: Health care trainees/students lack knowledge and skills for the comprehensive clinical assessment and management of pain. Moreover, most teaching has been limited to classroom settings within each profession.